Lecture Notes in Mathematics
DOI: 10.1007/bfb0091633
|View full text |Cite
|
Sign up to set email alerts
|

Conjugates of shimura varieties

Abstract: This is an introduction to the theory of Shimura varieties, or, in other words, to the arithmetic theory of automorphic functions and holomorphic automorphic forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(66 citation statements)
references
References 10 publications
0
65
0
1
Order By: Relevance
“…Si Y(T ′′ ) désigne le groupe de co-caractères d'un tore T ′′ , cette dernière condition est en faitéquivalentè a la surjectivité de l'application Y(T ) → Y(T ). La construction suivante, dite d'une zextension de G, est un cas particulier de [MS,Prop. 3.1].…”
Section: Ecrivons Maintenant Hunclassified
“…Si Y(T ′′ ) désigne le groupe de co-caractères d'un tore T ′′ , cette dernière condition est en faitéquivalentè a la surjectivité de l'application Y(T ) → Y(T ). La construction suivante, dite d'une zextension de G, est un cas particulier de [MS,Prop. 3.1].…”
Section: Ecrivons Maintenant Hunclassified
“…11 The authors found [39,40] and [41] useful in learning Shimura variety, connected Shimura variety, and Mumford-Tate group, respectively. 12 For an extension field E over F , Res E/F (G m ) is an Abelian group identical to E × = E\{0}.…”
Section: André-oort Conjecture and Coleman-oort Conjecturementioning
confidence: 99%
“…In this article, we just simply ignore this subtlety by tensoring Q. 39 We only consider Abelian varieties with a principal polarization in this article.…”
Section: Complex Multiplication On a Simple Abelian Varietymentioning
confidence: 99%
“…For a general G, choose a central extension ν : H → G such that H der is simply-connected, and S := Ker(ν) is a split torus (see [MS,Prop. 3.1]).…”
Section: A1 Proof Of Lemma 22mentioning
confidence: 99%